Grammar School in Baghdad, Andalusia, Egypt and Syria المدرسة النحوية في بغداد والأندلس ومصر والشام - Umar Manshur (JURNAL IJ-ATL, 2018)
Historically, Arabic grammatical studies had developed in Basra city. Then, the capital of Islam moved to Kufa. There was new genre  along with this movement. Next, since Abu Ja’far Al-mansur led Baghdad, some expert of Arabic grammar from Kufa and Basra met. So, Baghdadian discussed and compared those genres to make new genre. Meanwhile, Andalusian studied Arabic grammar in Middle East and new genre. After the Kindom of Baghdad ruined, some Arabic expert from Baghdad went to Egypt and Syria and taught there. They wrote Arabic grammar books and other knowledge as well.إن دراسة النحو في العرب تطورت بتطور الخلافة الإسلامية، حيث تطورت الدراسة النحوية في بغداد بعد أن كانت مدينة بغداد عاصمة في عصر خلافة أبي جعفر المنصور، فاتجه إليها نحاة الكوفة ودرس النحو فيها واتجه إليها بعد ذلك نحاة البصرة. فظهرت المناقشة النحوية بين مذهبي البصرة والكوفة في بغداد، ويوازن أهل بغداد بين أراء المذهبين وأخذوا الأرجح منها وجعلوه مذهبا لهم. والأندلسيون يرحلون إلى مدن الدولة العربية يتعلمون فيها النحو فاستحدثوا مذهبا رابعا بعد مذهب البصرة والكوفة والبغداد. واتجه النحاة بعد سقوط بغداد إلى مصر والشام ودرسوا النحو وكتبوا كتبا كثيرة في النحو والعلوم الأخرى.